(untitled) (Journal of Governance and Development (JGD), 2025)
Since the rise of the nation-state and global trade, natural resources have significantly shaped national economies and played a key role in determining economic growth and power. In Africa, however, the presence of resources and wealth has often failed to translate into sustainable development. Nigeria, despite its vast oil reserves, remains trapped in underdevelopment due to systemic inefficiencies and over-reliance on crude oil. This study examines Nigeria’s post-subsidy political economy, with a focus on the 2023 fuel subsidy removal under the Tinubu administration. Although intended to spur growth and attract investment, the policy has coincided with rising poverty, inflation, and economic stagnation. The research explicitly examines how Nigeria’s reliance on oil revenue, corruption, and import dependence affects economic diversification, stability, and development. It also examines the relationships between unemployment, inequality, insecurity, and their combined impact on Nigeria’s socio-economic development. Drawing on resource curse and conflict theory, and employing a mixed-methods approach, the study identifies political and administrative corruption, as well as low productivity, as key structural barriers to economic transformation. It argues that political corruption erodes institutional capacity, while unproductivity stems from poor resource usage and lack of diversification. The study recommends institutional reform, particularly in fiscal oversight, to bridge the gap between policy goals and developmental outcomes in resource-rich states like Nigeria. By offering a critical reappraisal of Nigeria’s resource governance, this study contributes new insights into the persistent gap between policy intentions and developmental outcomes in resource-rich states.